2013
DOI: 10.1007/s00418-013-1161-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical imaging of lipid droplets in muscle tissues using hyperspectral coherent Raman microscopy

Abstract: The accumulation of lipids in non-adipose tissues is attracting increasing attention due to its correlation with obesity. In muscle tissue, ectopic deposition of specific lipids is further correlated with pathogenic development of insulin resistance and type 2 diabetes. Most intramyocellular lipids are organized into lipid droplets (LDs), which are metabolically active organelles. In order to better understand the putative role of LDs in pathogenesis, insight into both the location of LDs and nearby chemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…110 Note that the differences in the spectra are subtle, yet are sufficient for a reliable mapping of functional units in the tissue. These are the types of applications where the imaging properties of CRS are in full effect: label-free chemical contrast, fast image acquisition, and (sub)micrometer resolution.…”
Section: Tissuesmentioning
confidence: 99%
“…110 Note that the differences in the spectra are subtle, yet are sufficient for a reliable mapping of functional units in the tissue. These are the types of applications where the imaging properties of CRS are in full effect: label-free chemical contrast, fast image acquisition, and (sub)micrometer resolution.…”
Section: Tissuesmentioning
confidence: 99%
“…Hyperspectral CARS was used to study lipid storage in muscle tissue (125) and identify cholesterol crystals from condensed aliphatic lipids in atherosclerotic plaques in mouse model (126). Suhalim et al (26) showed that the structure of crystalized cholesterol in plaques can be analyzed by integrating SRS microscopy with second harmonic generation modality (Figure 4 d ); Wang et al (74) discriminated cholesterol crystals from lipids in the pig model, and further quantified the cholesterol ester level and the degree of unsaturation in lipid droplets, by hyperspectral SRS.…”
Section: Frame-by-frame Hyperspectral Coherent Raman Scattering Micromentioning
confidence: 99%
“…9,10 In particular, the three techniques of coherent antiStokes Raman scattering (CARS), two-photon excited fluorescence (TPEF), and second-harmonic generation (SHG) microscopy are most widely employed for biomedical imaging. [11][12][13] Because each modality has different contrast mechanisms and images different biomolecular components, combining those multiphoton microscopies in one platform would make it possible to observe the proportions of various biomolecules.…”
mentioning
confidence: 99%